2019
DOI: 10.3390/rs11091133
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Photo-Based Measurement System to Calculate the Debarking Percentages of Processed Logs

Abstract: Within a research project investigating the applicability and performance of modified harvesting heads used during the debarking of coniferous tree species, the actual debarking percentage of processed logs needed to be evaluated. Therefore, a computer-based photo-optical measurement system (Stemsurf) designed to assess the debarking percentage recorded in the field was developed, tested under laboratory conditions, and applied in live field operations. In total, 1720 processed logs of coniferous species from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The measurement system was based on a photo-optical evaluation system that used one picture of every stem and estimated the rest of the stem surface. Tests showed that the average debarking percentage is very precise over a larger sample size (n > 20) (Heppelmann et al 2019b). However, the downside was that the individual values have only limited significance, since in the photo-optical analysis only a maximum of 50% of the total surface was displayed and actually measured.…”
Section: Field Sampling and Equipmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The measurement system was based on a photo-optical evaluation system that used one picture of every stem and estimated the rest of the stem surface. Tests showed that the average debarking percentage is very precise over a larger sample size (n > 20) (Heppelmann et al 2019b). However, the downside was that the individual values have only limited significance, since in the photo-optical analysis only a maximum of 50% of the total surface was displayed and actually measured.…”
Section: Field Sampling and Equipmentmentioning
confidence: 99%
“…Logs varied between 2.4 and 5.4 m in length, and diameters ranged from 8.0 to 54.7 cm. Following these measurements, a single picture per log (broadside) was taken with a reflex camera mounted on a tripod set at a height of 1.50 m above ground (Heppelmann et al 2019b). The camera was moved after every picture and relocated to the next log.…”
Section: Field Sampling and Equipmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The modification of feed rollers is represented by the replacement of spikes or horizontal roller ribs with spiralized ribs [22,24]. Thanks to this improvement, the stem rotates around its longitudinal axis while being processed, thus helping the debarking knives remove bark more perfectly from the entire stem surface [25]. Furthermore, if these modified feed rollers have an added wider and less aggressive length measuring wheel, we can describe another category whose representative is John Deere with the H480C head [23].…”
Section: Introductionmentioning
confidence: 99%